2018
DOI: 10.4269/ajtmh.17-0685
|View full text |Cite
|
Sign up to set email alerts
|

African and Asian Zika Virus Isolates Display Phenotypic Differences Both In Vitro and In Vivo

Abstract: Zika virus (ZIKV) is a mosquito-borne member of the genus that has emerged since 2007 to cause outbreaks in Africa, Asia, Oceania, and most recently, in the Americas. Here, we used an isolate history as well as genetic and phylogenetic analyses to characterize three low-passage isolates representing African (ArD 41525) and Asian (CPC-0740, SV0127-14) lineages to investigate the potential phenotypic differences in vitro and in vivo. The African isolate displayed a large plaque phenotype (∼3-4 mm) on Vero and HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 66 publications
3
58
0
Order By: Relevance
“…Indeed, recent studies have reported that ZIKV NS5 proteins from African and French Polynesian isolates antagonize IFNAR signaling by targeting STAT2 for degradation . However, NS5 and other ZIKV proteins from virus strains associated with the latest outbreak in Brazil have not yet been analyzed in this context, which is important given that Zika virus isolates differ significantly in in vivo and in vitro infection settings . Additionally, ZIKV infection has been suggested to prevent STAT1 and STAT2 phosphorylation .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have reported that ZIKV NS5 proteins from African and French Polynesian isolates antagonize IFNAR signaling by targeting STAT2 for degradation . However, NS5 and other ZIKV proteins from virus strains associated with the latest outbreak in Brazil have not yet been analyzed in this context, which is important given that Zika virus isolates differ significantly in in vivo and in vitro infection settings . Additionally, ZIKV infection has been suggested to prevent STAT1 and STAT2 phosphorylation .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of human outbreaks associated with the African lineage of ZIKV until now 27 is paradoxical because a large majority of experimental studies have found a higher transmissibility and pathogenicity of the African ZIKV strains relative to their Asian counterparts [28][29][30][31][32][33][34] . We hypothesized that this discrepancy could have reflected the lack of recent, low-passage African strains available for experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a growing body of experimental evidence, both in vitro and in vivo, points towards a higher transmissibility and pathogenicity of the African ZIKV strains compared to their Asian counterparts. African ZIKV strains typically cause more productive and more lethal infections than Asian strains in cell culture [28][29][30][31][32][33][34] , they are more transmissible by mosquitoes [35][36][37][38][39] and they are associated with more severe pathology in adult mice and mouse embryos 34,[40][41][42][43][44][45][46][47][48] . A few studies, however, reported evidence supporting the opposite conclusion in non-human primates [49][50][51] , various cell types 52,53 and mosquitoes 47 .…”
Section: Introductionmentioning
confidence: 99%
“…African and Asian ZIKV strains are associated with phenotypic differences in both in vitro replication and in vivo pathogenesis (2831). The Rio-U1 ZIKV stock used in this study was a primary stock isolated from a Brazilian patient and is not adapted to cell culture.…”
Section: Discussionmentioning
confidence: 99%